Overview of the plant protection products and other products suitable for organic production - Matej Orešković; Andrijana Galić (Glasnik Zaštite Bilja, 2023)
Organic plant protection 2023. contains overview of both amateur and professional plant protection products, enhancers, pheromones, repellents and other products suitable for use in organic production. The formulation, the active substance, the manufacturer / distributor and the way of applying the products are listed in the overview. Since organic production is demanding and use of certified products is needed, the recommendation is to require an eco-certificate from the manufacturer or dealer in advance. Any application of plant protection products as well as other products in any manner other than specified in the instructions for use and on the label shall be considered performed exclusively at one's own risk.